Tacrolimus: Influence of the Posttransplant Concentration/Dose Ratio on Kidney Graft Function in a Two-Year Follow-Up - Maja Nowicka; Monika Górska; Zuzanna Nowicka; Krzysztof Edyko; Piotr Edyko; Sebastian Wiślicki; Anna Zawiasa-Bryszewska; Janusz Strzelczyk; Józef Matych; Ilona Kurnatowska (Karger Publishers, 2019)
Introduction: Tacrolimus (TAC) metabolism rate has the potential to impact graft function after kidney transplantation (KTx). We aimed to analyze the relationship between the early post-KTx TAC C/D ratio (blood trough concentration normalized by total daily dose) and kidney graft function in a 2-year follow-up. Methods: We retrospectively analyzed data from 101 post-KTx patients at 3, 6, 12, and 24 months after KTx to identify the C/D ratio cutoff value optimal for dividing patients into fast and slow TAC metabolizers. We investigated the relationship between their TAC metabolism rate and graft function. Results: Patients were divided based on the TAC C/D ratio at 6 months after KTx of 1.47 ng/mL * 1 mg. Fast metabolizers (C/D ratio <1.47 ng/mL * 1 mg) presented with significantly worse graft function throughout the whole study period (p < 0.05 at each timepoint) and were significantly less likely to develop good graft function (estimated glomerular filtration rate ≥45 mL/min/1.73 m2) than slow metabolizers. Our model based on donor and recipient age, recipient sex and slow/fast metabolism status allowed for identification of patients with compromised graft function in 2-year follow-up with 66.7% sensitivity and 94.6% specificity. Conclusion: Estimating TAC C/D ratio at 6 months post-KTx might help identify patients at risk of developing deteriorated graft function in a 2-year follow-up.